Discharge Planning Pada Rehospitalisasi Pasien Congestive Heart Failure (CHF) - Nurul Hidayah; Dian Aulia Kurniawati; Dewi Siti Nurkhasanah Umaryani; Novi Ariyani (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Objective: to analyze a correlation of Congestive Heart Failure (CHF) discharge planning and readmission after hospitalization.Methods: The study was conducted at ICCU Tidar Magelang hospital with 27 Congestive Heart Failure (CHF) patients who had readmission after hospitalization. The sampling technique was done by consecutive sampling technique. Data analysis in this study using Chi square. Results: The results of the statistical test (Chi Square) show that 1 cell (25,0%) with an expected value <5 means that the cell (box) with the expected value is below 5 is 25,0%. The minimum expected value is 2,96 meaning that there is no expected value <1. Continuity correction with p value = 0,002. The p-value of Fisher's Exact Test = 0,001. The results of the Symmetric Measures table (correlation test) obtained the value of the Contingency Coefficient (r) = 0,561 with a value of p = 0,000.Conclusion: The conclusion of this statistical test is that there is a correlation of Congestive Heart Failure (CHF) discharge planning and readmission after hospitalization.Keywords: Congestive Heart Failure, Discharge Planning, Readmission, Hospitalization